2006
DOI: 10.1007/s10295-006-0185-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficient solubilization, purification of recombinant extracellular α-amylase from pyrococcus furiosus expressed as inclusion bodies in Escherichia coli

Abstract: The gene encoding the Pyrococcus furiosus extracellular alpha-amylase (PFA) was amplified by PCR from P. furiosus genomic DNA and was highly expressed in Escherichia coli BL21-Codon Plus (DE3)-RIL. The recombinant alpha-amylase was mainly expressed in the form of insoluble inclusion bodies. An improved purification method was established in this paper. The solubilization of the inclusion bodies was achieved by 90 degrees C treatment for 3 min in Britton-Robinson buffer at pH 10.5. The solubilized PFA was then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…2b large aggregates of more than 300 kDa were also observed in native conditions with no heat treatment. It was previously reported that high accumulation of recombinant proteins in plant chloroplasts leads to the formation of inclusion bodies [25]; PFA accumulates in inclusion bodies in E. coli , and requires refolding for activity [7]. Our results suggest that ER-targeted plant-made PFA is correctly folded since aggregates are enzymatically functional, obviating the need for refolding, thus facilitating the process and reducing the cost of PFA production.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…2b large aggregates of more than 300 kDa were also observed in native conditions with no heat treatment. It was previously reported that high accumulation of recombinant proteins in plant chloroplasts leads to the formation of inclusion bodies [25]; PFA accumulates in inclusion bodies in E. coli , and requires refolding for activity [7]. Our results suggest that ER-targeted plant-made PFA is correctly folded since aggregates are enzymatically functional, obviating the need for refolding, thus facilitating the process and reducing the cost of PFA production.…”
Section: Resultssupporting
confidence: 54%
“…PFA's advantages over α-amylases from other sources include an optimal temperature of 100 °C, a half-life of 13 h at 98 °C, and Ca 2+ -independent functionality. PFA is very desirable in industrial applications, but its use is hampered by the high production cost in E.coli because it accumulates in the form of insoluble inclusion bodies, and a tedious solubilization procedure is required to produce a soluble functional enzyme [7]. Over the years, there has been interest in exploring new strategies to increase the solubility and yield of recombinant PFA.…”
Section: Introductionmentioning
confidence: 99%
“…This added Ca 2ϩ inhibits the activity of glucose isomerase, which is used in later steps for isomerization of glucose to fructose during high-fructose syrup production (29). Calcium oxalate is also produced as a waste product and deposits in the pipes and heat exchangers.…”
Section: Discussionmentioning
confidence: 99%
“…The α-amylase activity was assayed according to Bernfeld and Wang et al (Bernfeld 1955;Wang et al 2007). Briefly, a 10 μl aliquot of suitably diluted enzyme was mixed with 490 μl sodium acetate buffer (50 mM, pH 5.5) containing 1 % soluble starch and incubated at 100°C for 15 min.…”
Section: Amylase Activity Assaymentioning
confidence: 99%
“…Due to the inherent difficulty to cultivate P. furiosus, sufficient production of this enzyme can only be achieved using recombinant expression. Previous studies indicated that recombinant PFA, when expressed at a high level, is always expressed as inclusion bodies (Dong et al 1997;Wang et al 2007). Several studies have tried to express PFA in its soluble form.…”
Section: Introductionmentioning
confidence: 99%